ANALISIS FAKTOR-FAKTOR RISIKO KEJADIAN PERDARAHAN POSTPARTUM: SCOPING REVIEW - Silvia, Neneng Wildan; Sulistyaningsih, Sulistyaningsih (Universitas Muhammadiyah Mataram, 2022)
Abstract: Background: Globally, postpartum hemorrhage remains the leading cause of maternal death. It is still a problem internationally as well as Indonesia. Given that many studies that have been done with the opposite results, it is necessary to do a scooping review on postpartum bleeding risk factors for prepartum screening. Objective: To analyze risk factors related to postpartum hemorrhage incidents. Method: Scoping review consisted of five stages of identifying research questions with the PEOS framework. Articles published from 2010-2020 were identified using relevant databases (PubMed, Science Direct, and Wiley) with keywords. The article selection employed a critical appraisal; afterward, it was inserted in the prism flowchart. Results: The database search in 765 articles screened the relevance of titles and abstracts, and it found ten A-grade articles. Conclusion: Risk factors that contribute to postpartum hemorrhage were from maternal factors, namely history of postpartum bleeding, maternal age ≥40 years, fetal risk factors, namely multiple pregnancies, infant macrosomia, clinical risk factors of MgSO4 administration, and placenta retention.Abstrak: Larat belakang: Secara global, perdarahan postpartum tetap menjadi penyebab utama kematian ibu. Hal tersebut masih menjadi masalah di internasional maupun Indonesia. Mengingat banyak penelitian yang sudah dilakukan dengan hasil yang berlawanan perlu dilakukan scooping review tentang faktor risiko perdarahan postpartum untuk dilakukan skrining sebelum persalinan. Tujuan: Menganalisis faktor-faktor risiko yang berhubungan dengan kejadian perdarahan postpartum. Metode: Scoping review terdiri dari lima tahapan yaitu mengidentifikasi research question dengan framework PEOS identifikasi artikel yang publikasi dari tahun 2010-2020 menggunakan database yang relevan (Pubmed, Science Direct, dan Wiley,) dengan kata kunci. Seleksi artikel menggunakan critical Appraisal setelah itu dimasukkan ke dalam prisma flowchart. Hasil: Pencarian di database 765 artikel setelah dilakukan penyaringan judul dan relevansi abstrak, didapatkan 10 artikel yang mempunyai grade A. Simpulan: Faktor risiko yang berkontribusi pada perdarahan postpartum dari faktor ibu, yaitu riwayat perdarahan postpartum, umur ibu ≥40 tahun, faktor risiko janin yaitu kehamilan ganda, bayi makrosomia, faktor risiko klinis pemberian MgSO4, dan retensi plasenta.